PERLINDUNGAN PENCARI SUAKA - Bambang Purwanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
As part of the international community in every state is obliged to respect and endeavor to ensure the protection of human rights of asylum seekers . Protection of asylum seekers have been set in the 1951 Convention and the 1967 Protocol to the restrictions that among other things for reasons of race, religion, nationality, membership in social groups any particular and members of certain political parties are outside the State not for economic reasons especially since she has committed a criminal act against peace, a war criminal offense or a crime against humanity.